2018
DOI: 10.1111/bre.12321
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of drainage dynamics influence on sediment routing system in a fold‐and‐thrust belt

Abstract: Drainage networks link erosional landscapes and sedimentary basins in a source‐to‐sink system, controlling the spatial and temporal distribution of sediment flux at the outlets. Variations of accumulation rates in a sedimentary basin have been classically interpreted as changes in erosion rates driven by tectonics and/or climate. We studied the interactions between deformation, rainfall rate and the intrinsic dynamics of drainage basins in an experimental fold‐and‐thrust belt subjected to erosion and sedimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 82 publications
(145 reference statements)
2
15
0
Order By: Relevance
“…R. Reitano et al: Erosional response of granular material in landscape models bounding a double-verging orogenic wedge (Braun and Yamato, 2010); the coupling between climate, erosion and tectonics (e.g., Batt and Braun, 1999;Beaumont et al, 1992Beaumont et al, , 2001Beaumont et al, , 2004Jamieson et al, 2004;Ueda et al, 2015;Whipple and Meade, 2004); the interaction between surface processes and multilayer folding systems (Collignon et al, 2014); the role of orographically enhanced precipitation in a double-verging 2-D model (Willett, 1999;Willett et al, 1993); the control exerted by tectonic strain (Castelltort et al, 2012;Duvall and Tucker, 2015;Goren et al, 2015); and interaction with tectonics in three dimensions (Ueda et al, 2015). Nevertheless, the computational capacities necessary to realistically simulate geologic features coupled with erosion using complex rheologies and/or three-dimensional settings still place strong limitations on numerical runs.…”
Section: Introductionmentioning
confidence: 99%
“…R. Reitano et al: Erosional response of granular material in landscape models bounding a double-verging orogenic wedge (Braun and Yamato, 2010); the coupling between climate, erosion and tectonics (e.g., Batt and Braun, 1999;Beaumont et al, 1992Beaumont et al, , 2001Beaumont et al, , 2004Jamieson et al, 2004;Ueda et al, 2015;Whipple and Meade, 2004); the interaction between surface processes and multilayer folding systems (Collignon et al, 2014); the role of orographically enhanced precipitation in a double-verging 2-D model (Willett, 1999;Willett et al, 1993); the control exerted by tectonic strain (Castelltort et al, 2012;Duvall and Tucker, 2015;Goren et al, 2015); and interaction with tectonics in three dimensions (Ueda et al, 2015). Nevertheless, the computational capacities necessary to realistically simulate geologic features coupled with erosion using complex rheologies and/or three-dimensional settings still place strong limitations on numerical runs.…”
Section: Introductionmentioning
confidence: 99%
“…Earth Surface Processes and Landforms, 43(15), 3152-3163. http://doi.org/10.1002/esp.4477 Chapter 3.1 "Drainage anomalies, or unusual patterns in river planform, can indicate recent river captures and reorganization of drainage networks, often in response to active tectonics (e.g. Bishop, 1995;Brookfield, 1998;Hallet and Molnar, 2001;Burrato et al, 2003;Clark et al, 2004;Delcaillau et al, 2006;Willett et al, 2014)". Since you cite Bishop 1995 here, who actually provides an in-depth examination of this issue, I would emphasise that the "can" is very important: indeed in the next sentence you explain "We mapped drainage anomalies across the study site and found abundant evidence of fluvial disruption within both domains.…”
Section: C4mentioning
confidence: 99%
“…Basin Research,8,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The rest of the chapters describes and quantifies to some extent drainage in the study area and examine the relation between drainage and the tectonic pattern. I regret a lack of use of recently utilised chi-maps (see papers by Willett's group for instance: Willett, S. D., McCoy, S. W., Perron, J. T., Goren, L., Chen, C. Y. (2014).…”
Section: C6mentioning
confidence: 99%
See 1 more Smart Citation
“…bounding a double-verging orogenic wedge (Braun and Yamato, 2010); the coupling between climate, erosion and tectonics (e.g., Batt and Braun, 1999;Beaumont et al, 1992Beaumont et al, , 2001Beaumont et al, , 2004Jamieson et al, 2004;Ueda et al, 2015;Whipple and Meade, 2004); the interaction between surface processes and multilayer folding systems (Collignon et al, 2014); the role of orographically enhanced precipitation in a double-verging 2-D model (Willett, 1999;Willett et al, 1993); the control exerted by tectonic strain (Castelltort et al, 2012;Duvall and Tucker, 2015;Goren et al, 2015); and interaction with tectonics in three dimensions (Ueda et al, 2015). Nevertheless, the computational capacities necessary to realistically simulate geologic features coupled with erosion using complex rheologies and/or three-dimensional settings still place strong limitations on numerical runs.…”
Section: Introductionmentioning
confidence: 99%